1994
DOI: 10.1073/pnas.91.5.1642
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of uracil from G.U mispairs by themismatch-specific thymine DNA glycosylase from HeLa cells.

Abstract: The uracil DNA glycosylases (EC 3.2.2.3) characterized to date remove uracil from DNA irrespective of whether it is base paired with adenine or mispaired with guanine in double-stranded substrates or whether it is found in single-stranded DNA. We report here the characterization of uracil glycosylase activity that can remove the base solely from a mispair with guanne. It does not recognize uracil either in A-U pairs or in single-stranded substrates. The enzyme, a 55-kDa polypeptide, was previously characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 30 publications
2
151
1
1
Order By: Relevance
“…MED1 Is Also Active on Uracil and 5-Fluorouracil Paired with Guanine-Both Mig.Mth and TDG have a mismatch-specific uracil glycosylase activity (22,31). Based on the similarities with these enzymes, we tested the uracil glycosylase activity of MED1 on oligonucleotide substrates in which uracil was paired with A, C, G, or T. As expected, MED1 uracil glycosylase activity is specific for G:U mismatches (Fig.…”
Section: Med1 Is a G:t Mismatch-specific Thymine Glycosylase-mentioning
confidence: 69%
“…MED1 Is Also Active on Uracil and 5-Fluorouracil Paired with Guanine-Both Mig.Mth and TDG have a mismatch-specific uracil glycosylase activity (22,31). Based on the similarities with these enzymes, we tested the uracil glycosylase activity of MED1 on oligonucleotide substrates in which uracil was paired with A, C, G, or T. As expected, MED1 uracil glycosylase activity is specific for G:U mismatches (Fig.…”
Section: Med1 Is a G:t Mismatch-specific Thymine Glycosylase-mentioning
confidence: 69%
“…The observation that Ugi inactivates these biologically distinct enzymes was not surprising because these proteins share 55.7% identical amino acid residues (23,26). In contrast, TDG, MED1, and SMUG, which do not share similar amino acid homology with UNG, are insensitive to inhibition by Ugi (13,18,27,28). Thus, addition of Ugi to cell-free extracts has been effectively used to investigate Ugisensitive and Ugi-insensitive modes of uracil-initiated BER (21,29).…”
mentioning
confidence: 98%
“…UNG preferentially recognizes uracil residues in single-stranded DNA and is also active on duplex DNA containing U⅐G mispairs and U⅐A base pairs (17). In contrast, human thymine-DNA glycosylase does not recognize uracil in single-stranded DNA but does excise uracil residues in double-stranded DNA with the following specificity: U⅐G Ͼ U⅐C Ͼ U⅐T Ͼ Ͼ U⅐A (18,19). The human MED1 (also termed MBD4) enzyme acts on U⅐G mispairs in the context of methylated or unmethylated CpG sites, but activity against uracil-containing single-stranded DNA and U⅐A, U⅐C, or U⅐T double-stranded DNA substrates was not detected (20).…”
mentioning
confidence: 99%
“…(51) Through an extensive purification, the eC-DNA glycosylase was identified as a 55 kDa polypeptide by SDS-PAGE, (52) which is the exact molecular mass of the previously purified human mismatchspecific T(U) Á G-DNA glycosylase, termed thymine-DNA glycosylase (TDG). (53) Moreover, the T Á G and U Á G mismatch glycosylase activities co-eluted with the eC activity in the same fractions, and competition studies suggested that they all reside in the same protein. (52) It was then proposed that eC is a substrate for hTDG.…”
Section: Excision Of Ecmentioning
confidence: 93%